Les regroupements d’objets comme aide à la compréhension du propos de l’exposition : enquête auprès des visiteurs du musée de La Cour d’Or – Eurométropole de Metz - Mathilde Champmartin (Les Cahiers de l'École du Louvre)
While an exhibition is above all an arrangement of objects in space, the question of the impact of that arrangement on visitors’ understanding has been of little interest to specialists. However, the simple choice of objects and their arrangement already tells them a great deal. A survey was carried out among visitors to the Cour d’Or Museum – Eurometropole in Metz to determine whether the grouping of objects helped them understand the purpose of the exhibition. After an examination of the methodology used, the results obtained are presented and possible solutions are proposed to resolve the difficulties.